ntegrasi Literasi Digital dalam PKn: Menanamkan Nilai-Nilai Etika Digital Peserta Didik - Megasari, Intan Indah (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2025)
His study aims to analyze the integration of digital literacy in Civic Education (Civics Education)learning in order to instill digital ethical values in students. In the rapidly growing digital era, students arefaced with complex ethical challenges in the use of technology. This research uses a qualitative method witha descriptive-qualitative study approach with a literature study approach, data sources are obtained fromthe results of analysis and conclusions obtained from journals. The results showed that the integration ofdigital literacy in Civics is effective in improving students' understanding of digital ethics. Through the useof relevant digital media, students learn about responsibility, privacy, security, and the social impact of theirdigital activities. In addition, Civics learning integrated with digital literacy helps students develop criticalthinking skills and the ability to make ethical decisions in a digital context. The implication of this study isthe importance of systematically integrating digital literacy in the Civics curriculum to equip students withthe digital ethics competencies needed in everyday life.Keywords: Digital Literacy, Civic Education, Digital Ethics, Students, Curriculum Integration